SAFe for DevOps practitioners : implementing robust, secure and scaled agile solutions with the continuous delivery pipelines /: implementing robust, secure and scaled agile solutions with the continuous delivery pipelines. (2023) - Wen, Robert; Koehnemann, Harry
No abstract available